The Influence of Sales Growth, Capital Structure and Tax Planning on Company Value (Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange 2018 - 2022): The Influence of Sales Growth, Capital Structure and Tax Planning on Company Value (Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange 2018 - 2022) - Dewanthi, Bernadetha Yessica; Purwatiningsih, Purwatiningsih (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine and test the effect of sales growth, capital structure and tax planning on company value in property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population is 88 companies. The method of determining the sample using purposive sampling, obtained 13 companies with a research period of 5 years so that the total research sample was 65. This study used secondary data sourced from company financial reports as data or research objects and tested the hypothesis using E-views 10 software as a test. The results showed that partially sales growth has an effect on firm value, capital structure has no effect on firm value and tax planning has an effect on firm value. Simultaneous testing of sales growth, capital structure and tax planning affect firm value.